Early rectal artesunate administration: a life-saver in remote areas?. (May 2009) - Grobusch, Martin P
Evaluation of: Gomes MF, Faiz MA, Gyapong GO et al. : Pre-referral rectal artesunate to prevent death and disability in severe malaria: a placebo-controlled trial. Lancet 373, 557––566 (2009). Malaria remains a major cause of morbidity and mortality in endemic areas, particularly in children under 5 years of age in sub-Saharan Africa. Distance to healthcare facilities is a key determinant of outcome. Gomes and colleagues report that pre-referral rectal artesunate administration significantly reduced permanent disability or death in patients still not receiving inpatient treatment after more than 6 h. In contrast, no significant effect was noted if treatment was administered within less than 6 h. With some questions remaining, this strategy appears to be an important, probably highly cost-effective additional tool urgently needed to help reducing the burden of disease.